2002
DOI: 10.1182/blood-2002-01-0128
|View full text |Cite
|
Sign up to set email alerts
|

Influence of plasma immunoglobulin level on antibody synthesis

Abstract: In previous experimental animal studies it has been demonstrated that antibody depletion is not followed by increased antibody synthesis. To assess whether these results are conferrable to antibody-depleted humans, we measured free light chains (flcs) as markers of current antibody synthesis in 8 patients treated with immunoadsorption (IA) therapy. Specific and bulk immunoglobulin levels were obtained simultaneously. The mean serum flc concentration increased to the preapheresis value within 1 day and remained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
3

Year Published

2004
2004
2011
2011

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 16 publications
0
13
0
3
Order By: Relevance
“…Therapeutic effects of PE or IA in autoantibody mediated diseases can be attributed to three major mechanisms: immediate intravascular reduction of (auto-)antibody concentration, pulsed induction of antibody redistribution, and subsequent immunomodulatory changes. The restoration of serum IgG levels after IA does not result from increased antibody synthesis but is related to changes of catabolism and immunoglobulin backflow [34]. The immediate improvement of clinical symptoms in Myasthenia gravis reflects the dynamic redistribution of AChRAb between neuromuscular synapses and intravascular spaces [23,24]; however, unlike in other diseases which directly depend on the absolute concentration of pathogenic factors, in Myasthenia gravis the absolute serum level of anti AChRAb has no strict correlation with disease severity especially in acute situations.…”
Section: Discussionmentioning
confidence: 96%
“…Therapeutic effects of PE or IA in autoantibody mediated diseases can be attributed to three major mechanisms: immediate intravascular reduction of (auto-)antibody concentration, pulsed induction of antibody redistribution, and subsequent immunomodulatory changes. The restoration of serum IgG levels after IA does not result from increased antibody synthesis but is related to changes of catabolism and immunoglobulin backflow [34]. The immediate improvement of clinical symptoms in Myasthenia gravis reflects the dynamic redistribution of AChRAb between neuromuscular synapses and intravascular spaces [23,24]; however, unlike in other diseases which directly depend on the absolute concentration of pathogenic factors, in Myasthenia gravis the absolute serum level of anti AChRAb has no strict correlation with disease severity especially in acute situations.…”
Section: Discussionmentioning
confidence: 96%
“…This reduction occurred despite ongoing IgG biosynthesis, which is regenerated at a constant rate regardless of IgG concentrations (25). In addition, it was shown that, once treatment was stopped, IgG levels eventually returned to concentrations that approached predose levels.…”
Section: Discussionmentioning
confidence: 97%
“…The relatively higher reduction of total serum IgG compared to Dsg-specific autoantibodies was presumably due to the redistribution of tissue-bound autoantibodies into the circulation. The rapid increase in Dsg-reactive IgG serum levels seen overnight during consecutive IA treatments suggests that a rediffusion of tissue-bound autoantibodies into the circulation may occur, since resynthesis is unlikely to cause the renewed increase in autoantibody titers [21]. To define a treatment protocol we examined the titers of anti-Dsg3 IgG prior to and immediately after each IA treatment.…”
Section: Discussionmentioning
confidence: 99%